Kelebihan Perampasan Aset dalam Putusan Perkara Pidana yang Menyasar Aset Milik Pihak Ketiga - Padlilah Padlilah (Jurnal Hukum Lex Generalis, 2026)
Asset forfeiture has become an essential legal instrument in combating crime by facilitating the recovery of state losses and depriving offenders of the economic benefits derived from criminal activities. Legal issues arise when the confiscated assets are owned or controlled by third parties who are not directly involved in the underlying offense, while the existing legal framework, particularly Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering, as well as other regulations governing asset forfeiture, does not provide adequate legal certainty regarding the protection of bona fide third parties. Furthermore, the Draft Law on Asset Forfeiture is expected to address these legal shortcomings; however, it still requires clearer provisions concerning evidentiary standards and legal safeguards for good-faith third parties. This study aims to analyze the legal framework governing asset forfeiture involving third parties under Indonesian positive law and to evaluate the urgency of strengthening such regulations through the Draft Law on Asset Forfeiture. This research employs a normative juridical method using statutory, conceptual and case approaches. The findings indicate that the current legal framework lacks explicit provisions concerning the legal status of third parties, the standards for proving good faith and effective objection mechanisms against asset forfeiture, thereby creating legal uncertainty. Therefore, the Draft Law on Asset Forfeiture should explicitly regulate the criteria for bona fide third parties, establish proportional evidentiary standards, provide effective objection procedures and harmonize its provisions with the Anti-Money Laundering Law to ensure both effective asset recovery and equitable legal protection.